Haemovigilance: A Current Update in Indian Perspective - Somnath Mukherjee; Rituparna Maiti (Journal of Clinical and Diagnostic Research, 2016)
Haemovigilance is an organised scheme of monitoring, identifying, reporting, investigating and analysing adverse events and reactions pertinent to transfusion and manufacturing blood products. This system is also an elemental part of quality control in a blood system, bringing about corrective and preventive measures, and for the perpetual advancement of the quality and safety of blood products and the transfusion process. Nowadays haemovigilance setups have been enforced throughout the globe in most developed countries, to monitor the adverse reactions and episodes associated with blood donations and transfusions. Indian Pharmacopoeia Commission has started a Haemovigilance Program of India (HvPI) in 2012 under its Pharmacovigilance Program of India (PvPI) in collaboration with National Institute of Biologicals, Noida, Uttar Pradesh, under Ministry of Health and Family welfare, Government of India with a primary objective to track adverse reactions/events and incidences associated with blood transfusion and blood product administration and to identify trends, recommend best practices and interventions required to improve patient care and safety. This review article is a detail update of current scenario of haemovigilance in India.